STRATEGY FOR DEVELOPING SEAWEEDS STICKS BUSINESS AT SINAR DUNIA INDUSTRY IN SANROBONE DISTRICT, TAKALAR REGENCY - Ashari Ashari; Marhawati Marhawati; Nur Halim; Muhammad Jufri; Sumiati Tahir (CV. ADIBA AISHA AMIRA, 2025)
Indonesia as an archipelagic country has great potential in the fisheries sector, especially seaweed cultivation which has high economic value and plays an important role in increasing the income of coastal communities. Takalar district in South Sulawesi is a potential area with most of the population relying on seaweed cultivation. However, this business faces various obstacles such as low income, limited information on business profits, to overcome these problems, community empowerment is carried out through training in processing seaweed into value-added products such as seaweed sticks. This research aims to identify strengths, weaknesses, opportunities, and threats and formulate appropriate development strategies to improve the competitiveness of seaweed stick products “Sinar Dunia” using qualitative methods through SWOT and AHP analysis. The results of this study show that the development strategy of Sinar Dunia Seaweed Sticks includes innovating flavor variants and product diversification to expand the market, improving packaging and consumer education through digital marketing, maintaining taste quality and production efficiency to face competition, as well as establishing partnerships with local farmers and including health information on packaging to reduce risk and increase competitiveness. From the above results, it can be concluded that Sinar Dunia Grass Sticks have great potential to be developed through product innovation, improved packaging, digital marketing, and cooperation with local suppliers, and need to overcome market weaknesses and threats in order to compete sustainably.